Catheter-directed interventions for pulmonary embolism - Zarghouni, Mehrzad (Cardiovasc Diagn Ther, 2016)
Pulmonary embolism (PE), a potentially life-threatening entity, can be treated medically, surgically, and percutaneously. In patients with right ventricular dysfunction (RVD), anticoagulation alone may be insufficient to restore cardiac function. Because of the morbidity and mortality associated with surgical embolectomy, clinical interest in catheter-directed interventions (CDI) has resurged. We describe specific catheter-directed techniques and the evidence supporting percutaneous treatments.